Pengembangan Kawasan Agropolitan Berbasis Komoditas Unggulan Apel Dalam Mengembangkan Ekonomi Lokal (Studi di Badan Perencanaan Pembangunan Daerah, Dinas Pertanian dan Kehutanan & Desa Tulungrejo Kecamatan Bumiaji Kota Batu) - Wati, Ria Tihana (Jurnal Administrasi Publik, 2014)
Abstract: The Development of Agropolitan Region Based on Apple Leading Commodity to Develop Local Economic (Study at Badan Perencanaan Pembangunan Daerah, Dinas Pertanian dan Kehutanan & Desa Tulungrejo Kecamatan Bumiaji Kota Batu). Result of research indicated that The Development of Agropolitan Region Based on Apple Leading Commodity at Desa Tulungrejo was using strategies to develop human resource and organization by training and counseling apple farmers and also providing the training session for the entrepreneurs of apple-based product industry, the development systems and works of agribusiness was oriented toward market strength (market driven) by improving the quality and quantity of apple and apple-based product, investment and capitalization were developed through providing capital grant or enlarging the access to capital for apple farmers and entrepreneurs of apple-based product industry and environmental friendly infrastructures were developed by deploying the equipments to support apple farming and apple-based product industry. The Development of Agropolitan Region Based on Apple Leading Commodity may give impact on the development of local economic at Desa Tulungrejo is increase of income obtained by apple farmers and entrepreneurs of apple-based product industry. Keywords: the development of agropolitan region, apple leading commodity, local economic development Â  Abstrak: Pengembangan Kawasan Agropolitan Berbasis Komoditas Unggulan Apel Dalam Mengembangkan Ekonomi Lokal (Studi di Badan Perencanaan Pembangunan Daerah, Dinas Pertanian dan Kehutanan & Desa Tulungrejo Kecamatan Bumiaji Kota Batu). Hasil dari penelitian ini menunjukkan bahwa Pengembangan Kawasan Agropolitan Berbasis Komoditas Unggulan Apel di Desa Tulungrejo dilakukan melalui strategi pengembangan sumber daya manusia dan kelembagaan melalui pelatihan dan penyuluhan kepada petani apel serta pelatihan kepada pelaku industri produk olahan apel, pengembangan sistem dan usaha agribisnis yang berorientasi pada kekuatan pasar (market driven) melalui peningkatan kualitas dan kuantitas apel dan produk olahan apel, pengembangan investasi dan permodalan melalui pemberian bantuan modal atau akses kredit kepada petani apel dan pelaku industri produk olahan apel serta pengembangan sarana dan prasarana berwawasan lingkungan melalui pemberian bantuan alat yang menunjang kegiatan budidaya pertanian apel dan industri produk olahan apel. Adanya Pengembangan Kawasan Agropolitan Berbasis Komoditas Unggulan Apel mampu memberikan dampak pada pengembangan ekonomi lokal di Desa Tulungrejo berupa peningkatan pendapatan yang diperoleh petani apel dan pelaku industri produk olahan apel. Â  Kata kunci: pengembangan kawasan agropolitan, komoditas unggulan apel, pengembangan ekonomi lokalÂ